Students’ Difficulties in English 7 Lessons: Inputs for Task-Based Supplementary E-Learning Materials Development and Evaluation - Enriquez, Jovy (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study aimed to determine the five most difficult learning competencies in English 7 which served as basis in developing and evaluating task-based supplementary e-learning materials for the Grade 7 students of Sto. Niño National High School, Division of Marikina City during the school year 2022-2023. The descriptive method of research was used with the achievement test and the survey questionnaire as the data gathering instruments. The sources of data were 43 Grade 7 students who took the achievement test, five English teacher experts who validated the questionnaire, 15 English teachers, and 12 English expert respondents from the different public schools in Marikina City, Pasig City, Antipolo City, and Rizal Province. The statistical tools used to treat the data were ranking, weighted mean, and t test.